Optimal Coordination of Overcurrent and Distance Relays Using Cuckoo Optimization Algorithm - Farhad Namdari; Sajad Samadinasab; Nader Shojaei; Mohammad Bakhshipour (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The duty of protective systems is the timely detection of fault and removing it from the power network. The accuracy of the results and reducing the execution time of the optimizing algorithm are two crucial elements in selecting optimizing algorithms in protective functions. The most important protective elements that are used in power networks are distance and overcurrent relays. In this article, a new algorithm is presented to solve the optimization problem of coordination of overcurrent and distance relays by using Cuckoo Optimization Algorithm which considers the non-linear model overcurrent relays at all stages of setting. The proposed method is tested on a standard 8-bus power system network. Also the results obtained have been compared with other evolutionary algorithms. The results show that the proposed approach can be provide more effective and practical solutions to minimize the time function of the relays and achieving optimal coordination in comparison with previous studies on optimal coordination of overcurrent and distance relays in power system networks.